Pengaruh Kualitas Layanan M-Banking dan Internet Banking Terhadap Kepuasan Nasabah PT. Bank Negara Indonesia (Persero) Tbk. Cabang Tanjungpinang - Romdoni, Mochammad Rizki; Nurul Saepul; Ratna Lia Usmanti (Jurnal Bangkit Indonesia, 2018)
This study aims to build a general model of a simulation system in maintaining and increasing customer satisfaction of PT Bank Negara Indonesia (Persero) Tbk's customers. Tanjungpinang through e-banking and internet banking services and produces the best scenario that can be used by policy makers in maintaining and increasing customer satisfaction of PT Bank Negara Indonesia (persero) tbk customers. Tanjungpinang through the quality of internet banking services. The dimensions of service quality used in this study are the dimensions of efficiency, reliability, responsiveness, privacy, security and fulfillment. Model development and simulation in this study uses a dynamic system. Dynamic systems represent the real world in the form of stocks, flow between stocks, and information that determines the value of the flow. The dynamic system model in this study describes the relationship of internet banking service quality to bank customer satisfaction and loyalty. The simulation results show that the quality of internet banking services plays an important role in maintaining and increasing bank customer satisfaction and loyalty. By increasing the value of the service quality dimension by 80% for each dimension, customer satisfaction and loyalty will increase so that it will increase bank income and profit. Therefore, to increase customer satisfaction and loyalty, all dimensions of the quality of internet banking services must be improved in line with the increase in the number of users and the number of internet banking transactions.